Factors Determining the Successful Implementation of New Information Technology in a Professional Union - Solomon, Norman; Templer, Andrew (Relations industrielles / Industrial Relations, 1992)
This paper investigates the successful implementation of information technology in a provincial teachers federation. The basic question explored is whether a labour organisation will make special efforts to implement information technology in a responsible and consultative fashion in order to harmonize the needs of two important stakeholders, its employees and its members, and if so, how those needs will be harmonized.